Fabrication, mechanical properties and failure mechanism of random and aligned nanofiber membrane with different parameters - Liu Su-dan; Li Dian-sen; Yang Ying; Jiang Lei (Nanotechnology Reviews, 2019)
Polyacrylonitrile (PAN) nanofiber membranes with different concentrations, rotary speeds and four kinds of aligned with fiber orientation of 0∘, 0∘/90∘, 0∘/90∘/+45∘ and 0∘/90∘/+45∘/−45∘ were prepared via electrospinning technique. The nanofiber membranes were morphologically characterized and mechanically tested. The results showed that nanofibers have uniform structure without any beads when the concentration increased 12wt%. The tensile strength and modulus of PAN nanofiber membranes increase with increasing the concentration. The orientation of nanofibers increases significantly with increasing rotary speed and fabricated nanofibers membrane has best orientation and tensile properties at 2500rpm. Moreover, the tensile properties can be affected greatly by the fiber structure and these decrease significantly with increasing the fiber orientation angle. The results also show that the nanofiber membranes exhibit obvious ductile fracture characteristics. Moreover, shear characteristics become more evident with increasing the concentration, and the failure mode changes from shear feature to flush fracture with increasing the rotary speed. In addition, the failure patterns vary with fiber structure and the main damage is in the form of interlayer delaminating, interface debonding, fibers tearing and breakage of the nanofibers.